2009
DOI: 10.1188/09.cjon.305-309
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Prostate Cancer Clinic for Newly Diagnosed Patients

Abstract: Newly diagnosed patients with prostate cancer have various treatment options, and a multidisciplinary prostate cancer clinic (MPCC) can present all options in a single setting. An MPCC was started in 2004 at the University of Texas M.D. Anderson Cancer Center, and 258 patients with prostate cancer were evaluated in its first year. The clinic expanded in 2006 and an oncology advanced practice nurse (APN) was recruited to address specific objectives. The APN role was used to implement a quality-of-life protocol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In the USA, for example, physician assistants have been in place since the 1960s, in an effort to address the national shortage of physicians in primary care as well as in rural areas . Across Europe, there are now approximately 2500 Urology nurse practitioners who belong to the European Association of Urology Nurses , providing a diverse range of urological services such as flexible cystoscopy , lower urinary tract assessment , prostate clinics and sexual dysfunction assessment clinics . Although the physician in charge is ultimately responsible for the care of their patients, it is clear that the role of the NPP has evolved and expanded considerably in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…In the USA, for example, physician assistants have been in place since the 1960s, in an effort to address the national shortage of physicians in primary care as well as in rural areas . Across Europe, there are now approximately 2500 Urology nurse practitioners who belong to the European Association of Urology Nurses , providing a diverse range of urological services such as flexible cystoscopy , lower urinary tract assessment , prostate clinics and sexual dysfunction assessment clinics . Although the physician in charge is ultimately responsible for the care of their patients, it is clear that the role of the NPP has evolved and expanded considerably in recent times.…”
Section: Discussionmentioning
confidence: 99%
“…5 Reports from other multidisciplinary clinics indicate high patient satisfaction similar to the levels at our clinic. 6 In establishing a multidisciplinary clinic, the need for the long-term commitments of all participants and the institution cannot be underestimated. Although the multidisciplinary setting is often viewed as an "inefficient" use of time in terms of the numbers of patients that can be seen by an individual clinician, we have demonstrated that there is a potential outcome benefit to many patients with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…3 Since that time, several other centers have developed similar programs. [4][5][6] Herein we report on findings from our KCC/TJU oncology data to explore the impact of our multidisciplinary efforts over the last 15 years and to describe changes to our original program.…”
Section: Introductionmentioning
confidence: 99%
“…2,21 In addition, reports from other MDCs indicate high patient satisfaction with this approach. 22 Of the 224 patients with high or very high risk, 13 (5.8%) and 42 (18.8%) were also managed conservatively or with primary ADT. While these numbers are not large, multiple randomized, controlled trials have shown that compared to RT and ADT, patients have an increased risk of PCa-related and overall mortality [23][24][25] and combined modality treatment should be offered.…”
Section: %)mentioning
confidence: 99%